2009
DOI: 10.1177/147323000903700129
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Brain Tumour Stem Cells in the Emergence of a Fast-Growing Malignant Meningioma after Surgical Resection and Radiotherapy of High-Grade Astrocytoma: Case Report and Preliminary Laboratory Investigation

Abstract: The case of a 62-year old man diagnosed with radiation-induced meningioma (RIM) after treatment for astrocytoma with an unusually short latency period of 7 months is reported. The patient first presented with a 2-month history of memory decline. Magnetic resonance imaging (MRI) showed a tumour in the left parieto-temporal lobe. Gross total resection was performed and the tumour was confirmed to be an astrocytoma. The patient received cranial radiotherapy 2 weeks later, however 7 months after radiation treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…We also used meningioma as additional positive control and comparison (Fig 2). Consistent with the literature,16,17 our data showed that meningioma was positive for CD133 and SDF-1 signals. Hemangioblastoma and meningioma appeared to be roughly similar to AVM tissues in the number of EPCs.…”
Section: Resultssupporting
confidence: 92%
“…We also used meningioma as additional positive control and comparison (Fig 2). Consistent with the literature,16,17 our data showed that meningioma was positive for CD133 and SDF-1 signals. Hemangioblastoma and meningioma appeared to be roughly similar to AVM tissues in the number of EPCs.…”
Section: Resultssupporting
confidence: 92%
“…Tumor stem cells are proposed to be the cellular origin of cancer including glioblastoma (GB) ( 3 ) and leukemia ( 4 ), are increasingly thought to be the origin of benign entities such as Dupuytren's disease ( 5 ), infantile hemangioma ( 6 ) and MG ( 1 , 7 9 ). Cultured MG cells form tumor spheres ( 8 ), demonstrate self-renewal, and express embryonic stem cell (ESC) associated markers including SOX2, nestin ( 1 ) and KLF4 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have documented the presence of cells with stem cell phenotype within MG, although their exact location has not been clearly defined ( 1 , 7 , 8 , 10 , 11 ). Stem cells are characterized by their expression of certain ESC-associated markers including OCT4, SOX2, NANOG, KLF4 and c-MYC.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic options for the treatment of patients with astrocytoma are limited to three fundamental modalities: surgical resection, chemotherapy, and radiation therapy [46]. Cellular adoptive immunotherapy with specific CTLs has been recently used to treat malignant tumors [79].…”
Section: Introductionmentioning
confidence: 99%